Potential-field data in integrated frontier basin geophysics: Successes and challenges on Australia's continental margin. (January 2015) - Hackney, R.; Goodwin, J.; Hall, L.; Higgins, K.; Holzrichter, N.; Johnston, S.; Morse, M.; Nayak, G.K.; Petkovic, P.
Abstract: Offshore frontier sedimentary basins are characterised by a lack of constraining geological and geophysical data. This lack of data is generally the result of deep water (>500 m), difficult geology (volcanics and salt), remoteness and harsh met–ocean conditions. These characteristics present significant challenges to marine surveying, which means that frontier basins tend to be underexplored. With continuing interest in exploration for energy resources in frontier regions, many frontier basins around the world have been the focus of increasingly-sophisticated geophysical studies that integrate a range of methodologies, including those based on potential-field (gravity and magnetic) data. Underexplored frontier basins around Australia's continental margin have received increased attention during the last decade, largely as a result of government-funded programs of precompetitive data acquisition and analysis. The components of this work that have relied heavily on potential-field data include: first-pass depth-to-basement estimation using spectral techniques applied to magnetic data; enhancement of gravity and magnetic images to aid the identification of basin depocentres and to facilitate onshore–offshore geological interpretation of basement structure; multi-scale edge-detection applied to gravity and magnetic data to aid the interpretation of basement structure; 3D forward and stochastic inverse modelling of gravity data to guide seismic interpretation of sediment thickness and basement structure; and using supercomputers for high-resolution, regional-scale 3D inverse modelling of magnetic and gravity data to constrain the physical properties of the crust. Despite the additional insight offered by this work, efforts to understand frontier basins are not without challenges, one of the most fundamental of which is to ensure that non-specialists are not misinterpreting data (e.g. wrongly interpreting artefacts arising from specific processing). The other main challenge in Australian frontier basins arises from a lack of constraints on crustal structure. This leads to significant ambiguity when using gravity data to infer sediment thickness or to understand the nature of basement. This ambiguity could be vastly reduced through the acquisition of seismic refraction data that focuses on imaging crustal structure. Further opportunities exist in using alternative methods for automated depth-to-basement estimation, incorporating process-oriented rather than static potential-field modelling, and in applying 3D forward and inverse gravity and magnetic modelling to other Australian frontier basins. Highlights: Frontier sedimentary basins lack seismic reflection and well data. Gravity and magnetic data have an important role in underexplored frontier basins. Australian margin lacks seismic refraction data for basement and crustal structure. Potential for more forward/inverse gravity/magnetic modelling incorporating process.